2005
DOI: 10.1249/01.mss.0000158186.32450.ec
|View full text |Cite
|
Sign up to set email alerts
|

Cold Air Inhalation Does Not Affect the Severity of EIB after Exercise or Eucapnic Voluntary Hyperventilation

Abstract: Similar postchallenge percent falls in FEV1 for room- and cold-temperature EVH and exercise suggest that dryness is essential to test conditions, as cold temperature did not have an additive effect to the EIB response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…This increased vasoconstrictor response then limits air flow. 103 A second theory suggests that the combination of cold air and increased breathing rate cools airways; after airways rewarm, increased blood flow leads to edema formation and airway flow reductions. 103 The reduction of airway flow reduces maximal ventilation and, subsequently, maximal performance.…”
Section: Predisposing Medical Conditionsmentioning
confidence: 99%
“…This increased vasoconstrictor response then limits air flow. 103 A second theory suggests that the combination of cold air and increased breathing rate cools airways; after airways rewarm, increased blood flow leads to edema formation and airway flow reductions. 103 The reduction of airway flow reduces maximal ventilation and, subsequently, maximal performance.…”
Section: Predisposing Medical Conditionsmentioning
confidence: 99%
“…Respiratory symptoms, such as coughing, wheezing, chest tightness and shortness of breath, are the most frequent complaints among adolescents and young adults. Asthma that develops during exercise is commonly called EIA [3][4][5][6][7] and is classifi ed as a reduction in lung function of >10% in FEV1 [8]. It is likely that most patients with asthma have been diagnosed based on symptoms alone, even though the disease is characterised by variable airway limitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the temperature of the inspired air has been subsequently shown to be unimportant to the degree of bronchoconstriction from this challenge. 38,39 Using dry ambient temperature air (228C) and dry cold air (218C), Evans et al 39 found no difference in post-EVH falls in FEV 1 between inhaled air temperature conditions (15.2 vs 13.8 for room temperature and cold air inhalation, respectively). Because the cold temperature inhaled air did not have an additive effect to the bronchoconstrictive response in this study, Evans et al 38 suggested that the water content and not temperature of the inhaled air is essential to test conditions.…”
Section: Eucapnic Voluntary Hyperpneamentioning
confidence: 99%
“…Airway water loss because of low RH inhaled air is the critical trigger that initiates the release of mediators leading to airway narrowing in susceptible individuals, and is thus a key Stensrud et al 53 demonstrated a 50% reduction in severity of EIB when comparing exercise challenge conditions of 40% to 95% RH at ambient temperature (24% and 12% falls in FEV 1 , respectively). Further studies by Evans et al [37][38][39] examined inhaled air temperature and the EIB response and noted that the severity of EIB was related to water content and not the coldness of inhaled air during the exercise challenge. In those studies, subjects exercised while breathing room temperature (228C) dry air or cold (218C), dry air where inhaled air water content was less than 5 mgÁL 21 air; exercising minute ventilations were equal between conditions.…”
Section: Laboratory Challengesmentioning
confidence: 99%